Making a Hand : The Art of H. D. Bugbee - Grauer, Michael R., 1961- (Book collections on Project MUSE., 2020)
"Bugbee avidly absorbed cowboy scenes and the lifestyle that birthed them. He filled his canvases with colorful, authentic images that capture the spirit of the American West of the early to mid-1900s, especially in and near his beloved Texas Panhandle. He arrived in Clarendon, Texas, in 1914, moving there from Massachusetts with his family at the urging of his uncle, T. S. Bugbee, a contemporary of Charles Goodnight. The fourteen-year-old Harold was fascinated by the Civil War exploits of his rancher uncle and developed a longing to be a cowboy. He helped his father with the 1,000-acre ranch the family purchased after moving from back East, and he eventually attended the Agricultural and Mechanical College of Texas, where he studied architectural drawing. Subsequently he enrolled at the Cumming School of Art in Des Moines, Iowa. He left after two years when the founder of the school told the young Texan that he had learned all the school had to offer. By the 1930s, Bugbee was providing pen-and-ink sketches for magazines such as Ranch Romances, Western Stories, Country Gentleman, and Field and Stream. His illustrations for a biography of Charles Goodnight initiated a long association with historian J. Evetts Haley. In 1951, Bugbee became art curator for the Panhandle-Plains Historical Society, a position he held until his death in 1963. Previously known primarily by reputation alone, Bugbee and his life and work are long overdue for wider consideration. This richly illustrated overview of the man and his art provides a valuable and entertaining resource for collectors and students of western and Texas art"--